(untitled) (Tzintzun. Revista de Estudios Históricos, 2016)
Since the 16th century, when the geographically small island served as a military base for the devastation of the Aztec empire by the Spanish conquerors, Cuba has always played a strategic role for the empires of the world. Although Cuba’s economic performance depended in general on its integration in the economic structures of the prevailing empires, during the last centuries the cosmopolitan elites of Havana always had some influence on the imperial officials in Madrid, Washington or Moscow.